Effect of Salvia officinalis and Zingiber officinaler Extracts on Some Physiological and Biochemical Parameters of Mice - Dabdoub, Banan R.; Abdulhadi, Haitham L. (Journal for Research in Applied Sciences and Biotechnology, 2023)
Background Sage and ginger are considered from the medicinal and aromatic herbs and as a treatment method in traditional medicine a variety of diseases and is also used as a spice for cooking. Methodology The treatments were divided into three groups for each extract of the plant extracts of sage and ginger. The first group was dosed with sage extract at the rate of 0.5 ml per day for thirty days and the second group with alcoholic extract after disposal, of alcohol in the same quantity and the latter was left without a control dose. The same process was repeated on the ginger plant, then the blood was drawn and the amount of sugar was measured in all the groups Blood was drawn a month after the mice were infused with plant extracts, and some tests were conducted that included checking blood sugar, cholesterol, triglycerides, urea and creatinine. The present study showed significant decrease in the level of blood sugar between 60 to 64 mg/100 for ginger plant and sage aqueous extract respectively, compared to the control group 110 mg/100 ml. Ginger and sage aqueous extract also significantly reduced the level of urea in the blood to 18.21 mg /100 ml compared to the control 40 mg / 100 ml. The present work found that both sage and ginger have a vital role in the treatment of various damage and diseases. This may well be a type of treatment as drug role.